Preaching Islamic revival in East Africa - Ahmed, Chanfi (Cambridge Scholars Publishing, 2018)
"This book deals with the new dynamics of Islam in East Africa (Tanzania, Kenya, Uganda, Sudan and Comoros) and its attempt to expand through various missionary activities"--Page 4 of cover